PENGARUH DISIPLIN KERJA, STRES KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DAN STAFF SDN 006 - Widya Wulansari; Ade Parlaungan Nasution (EQUILIBIRIA, 2015)
The purpose of this study was to examine and analyze whether there is influence work discipline, work stress and work motivation on the performance of teacher and staff SDN 006 Batu Aji. As the object of this study were theacers and staff SDN 006 Batu Aji with a sample of 25 teachers and staff who serve as the respondent. Statement that is used has been tested by the analysis factor and validity and reability with cronbach alpha and the instrument is valid and reliable or fit foruse as a research tool. The correlation (R) in this study with a value of 0,784 which is the relationship between independent variables and the dependent variable of 78,4%, meaning that work discipline, work stress and work motivation related to the performance of teachers and staff SDN 006 Batu Aji. While the coefficient of determination (R2) obtained a value of 0,615 means of the changes in the dependent variable (work discipline, work stress, motivation) can be explained by the performance. While the rest is explained by other factors not addressed in this study.Partial results of statistical calculations using t-test, that variable work discipline positive effect but not significant with a significance of 0,890. Strengthened on previous research that states discipline does not effect the performance of teachers (in Dwi, 2013). Work stress variable positive and significant impact with a signifinance of 0,006. work motivation positive and significant impact with a significance of 0,038. Results of statistical calculations simultaneously by using test-f, that variable work discipline, work stress, and motivation to work togethers positive and significant with a significance of 0,000.